2017
DOI: 10.1007/s13304-017-0503-3
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative platelet–lymphocyte ratio is an independent factor of poor prognosis after curative surgery for colon cancer

Abstract: Interaction between tumour and host triggers a systemic inflammatory response. This situation has been associated to cancer progression. Several peripheral blood inflammatory scores have been recently developed, as PLR. Data about the relationship between these scores and cancer prognosis are contradictory. Therefore, the aim of our work is to evaluate the capability of PLR to predict long-term outcomes (OS and RFS) in patients who underwent curative surgery for colon cancer. A retrospective study was designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Therefore, several systemic in ammatory-associated markers, such as C-reactive protein, lymphocyte-to-monocyte ratio, platelet-to-lymphocyte ratio, and NLR, have been used as outcome predictors [4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, several systemic in ammatory-associated markers, such as C-reactive protein, lymphocyte-to-monocyte ratio, platelet-to-lymphocyte ratio, and NLR, have been used as outcome predictors [4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing reports have shown that systemic in ammatory reactions increase the risk of cancer development [2,3]. A number of studies have focused on in ammation-related prognostic variables, such as C-reactive protein and albumin levels, platelet-to-lymphocyte ratio, and neutrophil-to-lymphocyte ratio (NLR), to identify patients at a high risk of colorectal cancer recurrence after primary surgery [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In colon cancer, systemic in ammation not only affects cytokines, but also promotes angiogenesis and metastasis formation [12]. Therefore, several systemic in ammatory-associated markers, such as C-reactive protein, lymphocyte-to-monocyte ratio, platelet-to-lymphocyte ratio, and NLR, have been used as outcome predictors [4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have focused on in ammation-based prognostic factors, such as C-reactive protein and albumin levels, platelet-to-lymphocyte ratio, and neutrophil-to-lymphocyte ratio (NLR), to identify patients at a high risk of colorectal cancer recurrence after primary surgery [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Other immuneinflammation indices, such as NLR, PLR, GARI and GPRI associated with HCC patient prognosis were calculated as previously described. [10][11][12][13] The cutoff values for preoperative GAR, PLR, NLR GAIR and GPIR were decided by applying receiver operating characteristic (ROC) curves and determining the maximum Youden index for each curve.…”
Section: Data Collectionmentioning
confidence: 99%